Synthesis, Optical and Electrochemical Properties of Novel Formazan Analogs Incorporated Fluorene Moiety. Issue 1 (2nd January 2023) - El Guesmi, Nizar
Abstract: A series of novel formazan analogs 4 a –e, having MeO, Me, Cl, NO2 at para / meta ‐position in 1‐phenyl ring was synthesized by treatment of 9‐fluorenone hydrazone 2 with a series of the hydrazonoyl chlorides 3 a –e . The molecular structure elucidation of all newly synthesized formazans was achieved by using elemental analyses as well as spectroscopic tools. The substituent and solvatochromic effects of formazan derivatives in seventeen solvents with different chemical and physical properties were investigated by absorption spectroscopy. A small band shift is obtained in the absorption maxima as a function of solvent, displaying a less sensitivity of compounds 4 a –e to solvent polarity. A noticeable variation in the absorption maxima (λmax ) values was observed by modifying the electronic characteristic and positions of the substituents. Furthermore, the electrochemical properties were adressed by cyclic voltammetry measurements, and the influence of electron‐donating and withdrawing nature of the substituents on electrochemical properties of formazan derivatives has been studied. In addition, computational studies on the formazan structures were performed using B3LYP functional in DFT method at the 6‐31G(d, p) basis set, and the energy values related to their frontier orbitals (HOMO, LUMO) were estimated. A variety of reactivity descriptors, namely, ionization potential (IP), electron affinity (EA), hardness ( η ), softness ( S ), chemical potential ( μ ), electronegativity ( χ ) and electrophilicity index ( ω ) have been determined via energies values of HOMO and LUMO. The experimental data and theoretical results showed a good correlation. Abstract : Formazans are important class of organic compounds that have drawn widespread attention due to their diverse chemical reactivities and broad spectrum of biological activities. In this work, novel formazan analogs incorporated fluorene moiety were synthesized and characterized and their electronic properties were studied by cyclic voltammetry and UV‐vis spectroscopy. This study constitutes a useful tool of qualitative comparative analysis and a framework which can be used in the conception of novel formazan derivatives as function on the targeted application.